2011
DOI: 10.1182/blood-2010-07-299248
|View full text |Cite
|
Sign up to set email alerts
|

An anti–PR1/HLA-A2 T-cell receptor–like antibody mediates complement-dependent cytotoxicity against acute myeloid leukemia progenitor cells

Abstract: PR1 (VLQELNVTV) is a human leukocyte antigen-A2 (HLA-A2)-restricted leukemiaassociated peptide from proteinase 3 (P3) and neutrophil elastase (NE) that is recognized by PR1-specific cytotoxic T lymphocytes that contribute to cytogenetic remission of acute myeloid leukemia (AML). We report a novel T-cell receptor (TCR)- IntroductionCD8 T cells specific for the human leukocyte antigen-A2 (HLA-A2)-restricted peptides WT1 and PR1, which are derived from the endogenous leukemia-associated antigens Wilms' tumor anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(163 citation statements)
references
References 50 publications
9
154
0
Order By: Relevance
“…LAAs such as WT1, PRAME, PR3, and BMI-1 in CML patients represent attractive targets for immunotherapy, [23][24][25][26][27][28][29] with efficacy demonstrated in vaccination, including dendritic cell vaccination, [30][31][32][33] and, more recently, T-cell receptor-mimic antibodies. [34][35][36] In support of these studies, we observed maximal restoration of immune recovery, as demonstrated by increased effector NK cell and T-cell immune responses, reduced PD-1 inhibitory molecule expression on CD4 1 and CD8 1 T cells, and reduced numbers of Mo-MDSC in MR 4.5 only, suggesting DMR may be the preferred threshold for future TFR studies to benefit from the improved effector immune responses. Therapeutic methods to enhance NK cell function and immunogenic CTL responses early or blocking aberrant PD-1 signaling may result in greater rate of success in TKI cessation studies.…”
Section: Discussionsupporting
confidence: 55%
“…LAAs such as WT1, PRAME, PR3, and BMI-1 in CML patients represent attractive targets for immunotherapy, [23][24][25][26][27][28][29] with efficacy demonstrated in vaccination, including dendritic cell vaccination, [30][31][32][33] and, more recently, T-cell receptor-mimic antibodies. [34][35][36] In support of these studies, we observed maximal restoration of immune recovery, as demonstrated by increased effector NK cell and T-cell immune responses, reduced PD-1 inhibitory molecule expression on CD4 1 and CD8 1 T cells, and reduced numbers of Mo-MDSC in MR 4.5 only, suggesting DMR may be the preferred threshold for future TFR studies to benefit from the improved effector immune responses. Therapeutic methods to enhance NK cell function and immunogenic CTL responses early or blocking aberrant PD-1 signaling may result in greater rate of success in TKI cessation studies.…”
Section: Discussionsupporting
confidence: 55%
“…Decrease in Pr20 binding was not due to instability of peptide/HLA-A2 complexes, as each peptide increased surface HLA-A2 over unpulsed T2 cells in the assay, indicating that the peptides complexed with and stabilized HLA-A2 ( Figure 1B). The data demonstrated that specific changes to the native peptide sequence can abrogate Pr20 binding, consistent with other reported TCRm (15,29). of leukemia in vivo (11).…”
Section: Pr20 Binds To Aly/hla-a2 Complexes In Prame/hla-a2-expressinsupporting
confidence: 79%
“…23 Although T cell-based therapies have been attempted against WT1-expressing cancers, monoclonal TCRm antibodies have several advantages over vaccines, TCR constructs, and adaptive T cells: ESKM can be produced and administered easily; and it has greater potency, more predictable and simpler pharmacokinetics, and high efficacy. Although several TCRm antibodies have been developed for other antigens, 24 none has entered human trials.…”
Section: Introductionmentioning
confidence: 99%